Maths-
General
Easy

Question

Solve the following by using the method of substitution
X = 4Y+1
2Y - 3X =  - 23

hintHint:

find y by substituting x (in terms of y) in the equation and find x by substituting value of  y in the equations.

The correct answer is: x = 9 ; y = 2


    Ans :- x = 9 ; y = 2
    Explanation
    ⇒  x = 4y +1  — eq 1
    2y-  3x = -23—- eq 2
    Step 1 :- find y by x = 4y + 1 in eq 2.
    2y -3 (4y + 1 ) =  -23 ⇒ 2y - 12y - 3 = -23
    ⇒ -10y =  3 -23 ⇒ -10y = -20
    ⇒ y = 2
    Step 2 :- substitute value of y and find x
    ⇒  x = 4y +  1⇒ x = 4 (2) +1
    ⇒   x = 8+1
    ∴  x = 9
    ∴  x = 9 and y =2  is the solution of the given pair of equations.